Severe relapse of SARS‐CoV‐2 infection in a kidney transplant recipient with negative nasopharyngeal SARS‐CoV‐2 RT‐PCR after rituximab. Issue 8 (1st March 2022) - Morel, Antoine; Imbeaud, Sandrine; Scemla, Anne; Péré, Hélène; Fourgeaud, Jacques; Amrouche, Lucile; Robillard, Nicolas; Planas, Delphine; Puech, Julien; Simon, Sylvie; Lanternier, Fanny; Bélec, Laurent; et al.
Abstract : Immunocompromised patients may experience prolonged viral shedding after their initial SARS‐CoV‐2 infection, however, symptomatic relapses after remission currently remain rare. We herein describe a severe COVID‐19 relapse case of a kidney transplant recipient (KTR) following rituximab therapy, 3 months after a moderate COVID‐19 infection, despite viral clearance after recovery of the first episode. During the clinical relapse, the diagnosis was established on a broncho‐alveolar lavage specimen (BAL) by RT‐PCR. The infectivity of the BAL sample was confirmed on a cell culture assay. Whole genome sequencing confirmed the presence of an identical stain (Clade 20A). However, it had an acquired G142D mutation and a larger deletion of 3‐amino‐acids at position 143–145. These mutations located within the N‐terminal domain are suggested to play a role in viral entry. The diagnosis of a COVID‐19 relapse should be considered in the setting of unexplained persistent fever and/or respiratory symptoms in KTRs (especially for those after rituximab therapy), even in patients with previous negative naso‐pharyngeal SARS‐CoV‐2 PCR. Abstract : A kidney transplant recipient who had received rituximab therapy suffers a severe relapse of COVID‐19 relapse three months after a moderate COVID‐19 infection, with confirmation of the presence of the identical strain by whole genome sequencing, albeit with several mutations in the N‐terminal domain.